Beyond domain-led conceptualizations of urban zero-carbon transitions - Andrew Sudmant; Matt Tierney; Andy Gouldson; Joule Bergerson (Academia Environmental Sciences and Sustainability)
Rapid, systemic change is needed to achieve zero emissions, but there is uncertainty about how or where to intervene in urban systems. Drawing on the work of Donella Meadows, we apply a Leverage Points Perspective to identify and characterize points of system-level intervention that emerge from a study of climate action in Calgary, Canada, which was unique in applying a mixed set of academic approaches. Reflecting on Meadows’ and other frameworks for conceptualizing complex systems change, we discuss the challenge of conceptualizing change, a task of unique urgency in the context of the climate emergency. Too frequently, we argue, approaches focus attention on specific modes or forms of action seen to have the greatest opportunity for affecting change in place of the complex chains of actors, objects, and processes that collectively are the key to a deep and sustaining transition. We conclude by exploring how the insights of the Leverage Points Perspective and other approaches can be brought together to inform practical action, and by examining how related theoretical work on provisioning systems and applied work on urban Climate Commissions may be drawn on to advance understanding of how to deliver urban systems change.